PREDIKSI KELULUSAN MAHASISWA DENGAN JARINGAN SYARAF TIRUAN - Rudy Ansari (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2016)
Graduation became a benchmark in the policy making college management. Can estimate the graduation students annually is needed to be known by the university. Moreover, this paper attempts to apply neural network algorithms in predicting graduation, the selected method to be used is the method of propagation. This method is widely used in the researchers predict a problem. The sample data in the application of this algorithm is data the students began class of 2010 up to 2013. With the third generation output is passed late, fast and timely. From the results of the learning algorithm used obtained good accuracy results with the architecture of the pattern formed is 12-9-3.